2006
DOI: 10.1577/t05-063.1
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Changes in Prey Preference and Foraging Ability of Yellow Perch: Insights Based on Relative Energetic Return of Prey

Abstract: Ontogenetic diet shifts are an important component of the early life history of many fishes. Successfully shifting diets affects not only individuals but also populations and communities. We experimentally quantified prey selection and feeding behavior of age‐0 yellow perch Perca flavescens to determine the sizes at which diet shifts occur and identify potential mechanisms driving these shifts. Yellow perch were provided three prey types (zooplankton, benthic invertebrates, and fish) at high‐ and low‐density c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 27 publications
1
32
2
1
Order By: Relevance
“…Diet shift to larger prey presumably occurs as an attempt to eat more energetically profitable organisms as predators increase in size, followed by increased growth rates (Werner & Gilliam, 1984). However, as prey size increases, so do encounter probability and handling time, while prey vulnerability decreases (Graeb et al, 2006). In the lake studied, size-related variations were observed in fish diet, especially regarding the most important prey items (i.e., galaxiids and crayfish).…”
Section: Discussionmentioning
confidence: 93%
“…Diet shift to larger prey presumably occurs as an attempt to eat more energetically profitable organisms as predators increase in size, followed by increased growth rates (Werner & Gilliam, 1984). However, as prey size increases, so do encounter probability and handling time, while prey vulnerability decreases (Graeb et al, 2006). In the lake studied, size-related variations were observed in fish diet, especially regarding the most important prey items (i.e., galaxiids and crayfish).…”
Section: Discussionmentioning
confidence: 93%
“…These results suggest that mysids are energetically more beneficial as prey items than are insects; this greater energy benefit could explain the black crappies' selection of A. almyra over dipteran pupae in Lake Monroe. A wide variety of fish diet studies has found selective predation of more‐profitable prey items, which increased or maximized net energy return (Mittelbach 1981; Galarowicz and Wahl 2006; Graeb et al 2006). The resulting increase in fish growth (Mittelbach 1983; ) is consistent with our observation that black crappies in Lake Monroe exhibited greater growth than fish in the other lakes.…”
Section: Discussionmentioning
confidence: 99%
“…The rate at which ontogenetic transitions through preferred prey types and sizes may vary across 285 populations and species. There are several well known accounts of species that quickly transition 286 through various invertebrate types to fish (Graeb et al 2006), but these abrupt changes in growth are 287 more likely to be the exception than the norm (Werner and Gilliam 1984). The VBGF and arguments 288 made here all assume constant relationships between weight and various ecological processes (e.g.…”
Section: Approach 193mentioning
confidence: 97%